Pemanfaatan Limbah Pecahan Keramik Dan Kapur Sebagai Bahan Pengganti Sebagian Semen Pada Produksi Paving Blok Ditinjau Dari Nilai Kuat Tekan Dan Penyerapan Air - Aldi Setiawan; Mohammad Saifuddin; Ragil Arman Maulana (Universitas Dr. Soetomo, 2023)
Along with the rapid development of neighborhood and residential roads in Pamekasan, it has an impact on increasing the use of paving bloks for roads and residential yards. With the large number of needs, it has an impact on the need for paving blok materials, namely cement and aggregate, so a substitute material is needed to reduce dependence on the use of the main material. One of the substitute materials that can be used is the utilization of ceramic and lime waste which has not been used so far. The use of crushed ceramic shards and lime as a partial replacement of cement is expected to have an effect on the compressive strength of paving bloks. Utilization of ceramic and lime shard waste is expected to provide the latest innovations in the world of construction going forward. In this test, it is planned to pave a rectangular blok measuring 21x10.5x6 cm, and tested at the age of 7 days and 28 days on each variation of the mixture. %, and 25% replacement of cement with ceramics and lime. From the results of testing the chemical content of ceramics, it was found that the lime (CaO) content was 5.95% and the chemical content of the lime was found to have a lime (CaO) content of 50.84%. The results of the compressive test for each variation resulted in an increase in compressive strength from each variation. The greatest addition of compressive strength was found in the 20% variation with the resulting compressive strength of 30.35 Mpa at the age of 7 days, and 31.18 Mpa at the age of 28 days.